Aplikasi Evaluasi Perkembangan Latihan Atlet Panahan Menggunakan Progressive Web Application - Eby Sofyan Fadly; Jian Budiarto (Puslitbang Sekawan Institute Nusa Tenggara, 2019)
Arrihu Archery is one of the archery clubs in the city of Mataram. Before taking the test to increase the level, participants will take part in the stabilization exercise in preparation for the exam. The problem faced was that the exercise carried out took a long time and the trainers had difficulty in monitoring the progress of the participants. This writing aims to accelerate the exercise and make it easier to monitor the training of participants. Therefore, it is necessary to build an Application to Evaluate the Development of Archery Athlete Exercises using Progressive Web Application. The design of this system is done by the waterfall methodology, which is a system development method that begins with planning, system design, making Web Service APIs, and creating Service Workers in the Progressive Web App application. The results that have been achieved in this study are the creation of applications to assist the stabilization training process and assist in monitoring the progress of trainees. This application is able to cache and be able to display pages offline. This application runs well on the google chrome browser version 43+